The Chinese version of the emergency nurses’ professional resilience tool: A translation and validation study - Yinsen Peng; Hanyue Zeng; Wenyi Qing; Yun Li; Tengxia Chen; Cailian Wang; Miao Peng; Shifang Mao (BMC Nursing)
Abstract Background A high level of professional resilience is a necessary quality for emergency nurses. It can help emergency nurses cope with work pressure and safeguard their physical and mental health. However, there is no specific tool in China to measure emergency nurses’ professional resilience. This study aimed to translate the Emergency Nurses’ Professional Resilience Tool (ENPRT) into Chinese and validate its psychometric properties among emergency nurses. Methods Translation and revision of the ENPRT was completed based on the Brislin Translation Model. Using convenience sampling to recruit 750 emergency nurses from 20 hospitals in Sichuan, China, to participate in the survey. Content and structural validity analyses were conducted to assess the scale’s validity. The scale’s reliability was assessed by Cronbach’s α Coefficient, Split-half reliability, and intraclass correlation coefficient (ICC). Results The Chinese version of the ENPRT (ENPRT-C) included 34 items with scale content validity index (S-CVI) of 0.979. Exploratory factor analysis extracted four factors explaining 62.740% of the total variance, with factor loadings ranging from 0.620 to 0.873. Confirmatory factor analysis results indicating that the revised 4-factor model was well fitted ( $$χ $$ 2/df = 1.211, RMSEA = 0.026, CFI = 0.980, GFI = 0.0901, IFI = 0.9820, and TLI = 0.978), with good structural validity. The Cronbach’s α Coefficient, Split-half reliability, and ICC values for the ENPRT-C were 0.930, 0.715, and 0.812, indicating the scale has good reliability. Conclusion The ENPRT-C has good psychometric properties and can accurately measure Chinese emergency nurses’ professional resilience.